Changes in ultrasound velocity in the plastic deformation of high-chromium steel - Barannikova S. A.; Bochkareva A. V. Anna Valentinovna; Lunev A. G. Alexey Gennadievich; Shlyakhova G. V. Galina Vitaljevna; Zuev L. B. Lev Borisovich (2016, 2016)
Title screen